LITERATUR REVIEW: HAKIKAT TUHAN DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Arivan Mahendra; Muhammad Wahyu Ilhami, Wiyanda Vera Nurfajriani, Karoma (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The Real and One Supreme Being, the Powerful and Omniscient Creator, the Eternal, the Decider of Destiny, and the Judge of the universe. Islam emphasizes the conceptualization of God as the Sole and Almighty. The concept and nature of God in Islam is very broad.The method used in this article is using library research, which is a method of collecting data by understanding and studying theories from various literatures related to research.In the context of discussing the nature or form of God, philosophers put forward five arguments, Cosmological Arguments, Ontological Arguments, Design Arguments, Moral Arguments and Teleological Arguments. Whereas in Islam, God as Ilah, Dan Malik and Allah with His Attributes of Perfection (Asmaul Husna). There are 3 things that humans need to remember to understand the existence of God, namely: Everything other than God, including the universe is always dependent on God, God the Great and Mighty is basically the Most Compassionate, and Things that definitely require the existence of a proper relationship between God and humans, namely the relationship between the Beloved and His servants, which consequently gives birth to the relationship between humans and humans. A person who has pure monotheism will be able to easily achieve the goals of Islamic religious education, namely creating a monotheistic Muslim with perfect faith and being able to transfer his religious values in everyday life and making a Muslim who behaves well in hablum minallah and hablum minannas.